The Use of Non-Observance Maxims that Trigger Implicature in Ganjar Pranowo’s Interview - Fadilah, Jihan Nurul; Dinda Syifa Saiddina; Cecep Agus (Universitas Pamulang, 2024)
This study aims to analyze the use of non-observance maxims that trigger implicatures in the interview with Ganjar Pranowo, a prominent political figure in Indonesia. Employing a qualitative approach, the primary data source utilized was Youtube video of the exclusive interview with Ganjar Pranowo by TvOne, which were transcribed for analysis. Drawing on Grice's theory of conversational implicature, highlighting the implicit meanings conveyed through deviations from the four maxims of effective communication: quantity, quality, relation, and manner, this research delves into Ganjar Pranowo's communication strategies, particularly focusing on deviations from the cooperative principles in communication. This study reveals that Ganjar Pranowo frequently employs particularized implicatures to convey additional messages beyond the literal meaning of his words. This approach not only adds layers of meaning but also showcases the strategic use of language to imply information indirectly. Additionally, the study identifies instances where Ganjar Pranowo deliberately limits the information provided during interviews, further complicating the interpretative process for listeners. These findings illustrate the complexity of human communication dynamics, where implied messages and implicit communication strategies significantly influence the understanding of spoken words. This study offers profound insights into Ganjar Pranowo's adept use of language and implicatures to communicate nuanced messages. It highlights the intricacies of human communication processes and the subtle dynamics of interaction between speakers, emphasizing the importance of context and inference in effective communication.